1966
DOI: 10.1172/jci105330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thoracic cava obstruction on response of proximal tubule sodium reabsorption to saline infusion.

Abstract: We have recently demonstrated that in the normal dog infusion of isotonic or hypertonic saline results in marked depression of sodium reabsorption in the proximal tubule (1). This depression is independent of the effect of saline infusion on filtration rate and is not blocked by reduction of filtration rate. Such depression in proximal tubule reabsorption appears to account for the diuresis known, from the studies of De Wardener, Mills, Clapham, and Hayter (2, 3) and others (4-7), to occur after saline infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1
1

Year Published

1968
1968
1984
1984

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 10 publications
3
29
1
1
Order By: Relevance
“…Although many factors have been implicated as responsible for sodium retention in the caval dog, it is clear from the experiments of other investigators that the increase in tubular sodium reabsorption cannot be totally explained on the basis of alterations in renal hemodynamics, renal vein pressure, or renal innervation (2,4,11). In the present experiments GFR and ERPF tended to be lower in caval dogs compared with normals during water and hypotonic NaCl diuresis.…”
Section: Methodscontrasting
confidence: 49%
See 1 more Smart Citation
“…Although many factors have been implicated as responsible for sodium retention in the caval dog, it is clear from the experiments of other investigators that the increase in tubular sodium reabsorption cannot be totally explained on the basis of alterations in renal hemodynamics, renal vein pressure, or renal innervation (2,4,11). In the present experiments GFR and ERPF tended to be lower in caval dogs compared with normals during water and hypotonic NaCl diuresis.…”
Section: Methodscontrasting
confidence: 49%
“…Moreover, it has been demonstrated that either acute or chronic constriction of the thoracic inferior vena cava inhibits or retards the natriuresis usually seen with salt loading (2,3). Micropuncture experiments of Cirksena, Dirks, and Berliner (4) suggest that sodium retention in the caval dog is mediated by an increased fractional sodium reabsorption along the proximal tubule. The possibility that sodium reabsorption is also increased at more distal sites of the nephron has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs with partial, chronic constriction of the thoracic inferior vena cava (chronic caval dog) develop salt and water retention, edema and ascites, and usually respond to acute saline loading with only, at best, a feeble natriuretic response (3,4). It has generally been felt that the minimal sodium excretion observed in chronic caval dogs under conditions of acute saline loading is due to maintenance of sodium reabsorption in the proximal tubule (5).…”
Section: Introductionmentioning
confidence: 99%
“…The micropuncture experiments which demonstrated that the failure of caval dogs to excrete sodium in response to acute volume expansion was due to maintenance of fractional sodium reabsorption in the proximal tubule were carried out in dogs with acute rather than chronic constriction of the thoracic vena cava (5). Under these conditions, the major changes in systemic hemodynamics, and severe depression of GFR which occurred could easily have explained the observed data.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the natriuresis which follows volume loading of the dog is largely due to a prompt decrease in the tubular reabsorption of sodium which is independent of mineralocorticoid activity (3)(4)(5)(6). In this same species production of experimental salt retention is accompanied by ablation of the tubular natriuretic response (7,8). These tubular natriuretic factors may be operative in normal man and of importance in the sodium homeostasis of patients with chronic renal disease (9, 10).…”
Section: Introductionmentioning
confidence: 99%